Queer theory challenges: ideology and ignorance in Eve Sedfwick‟s axioms (TEL Tempo, Espaço e Linguagem, 2019)
Abstract: In this paper I aim to think of connections among queer theory and the discussions of ideology, knowledge and ignorance with an eye to highlighting how queer debates feed themselves on the gaps of ideologies of competence (CHAUÍ, 2008) The intertwining of the aforementioned themes plays a central role in the discussion of the axioms proposed by Eve Sedgwick (1990) as instruments of reflection on queer theory in contemporary times.Keywords: Queer theory. Eve Sedgwick. Ideology. Ignorance.